Pattern transitions in diary data of MDD patients: a mixed-methods multiple case study of psychotherapy dynamics - Nordholt, Sontje; Garrison, Philipp; Aichhorn, Wolfgang; Ochs, Matthias; Schiepek, Günter (Frontiers in Psychology, 2024)
Aim: Mixed-methods approaches promise a deep understanding of psychotherapeutic processes. This study uses qualitative and quantitative data from daily diary entries and daily self-assessments during inpatient treatment. The aim of the study is to get an insight on similarities and differences of both types of data and on how they represent self-organized pattern transitions in psychotherapy. While complete correlation of results is not expected, we anticipate observing amplifying and subsidiary patterns from both perspectives. Methods and Materials: Daily, five MDD-patients wrote diaries and completed self-assessments using the Therapy Process Questionnaire, a questionnaire for monitoring change dynamics of psychotherapy. The data was collected using the Synergetic Navigation System, an online-tool for real-time monitoring. Diary entries of the patients described their experiences in everyday life. The qualitative text analysis was conducted using Mixed Grounded Theory, which provided categories representing the patients' ongoing experiences of transformation and stagnation. The time series data was analyzed using the Dynamic Complexity algorithm and the Pattern Transition Detection Algorithm. Results from qualitative and quantitative analyses were combined and compared. Following the process of data triangulation, the leading perspective came from the theory of selforganization. In addition to presenting the overall results for all five patients, we delve into two specific case examples in greater detail.Results: Specific and highly diversified diary entries of 5 patients were classified into the categories perceived pattern stability, noticing improvement, broadening the perspective, critical instability, and experiencing moments of Kairos. Patients not only reported on problems related to their disorder (e.g., lack of energy, hopelessness), but on phases and steps of change which could be related to the theory of self-organization (e.g., problem attractors, critical fluctuations, pattern transitions, Kairos). Qualitative and quantitative analysis provide important supplementary results without being redundant or identical.Data triangulation allows for a comprehensive and multi-perspective understanding of therapeutic change dynamics. Especially the different topics expressed in the diary entries help to follow micro-psychological processes, far away from being a simple reaction to interventions. The way patients experience themselves being in stability or instability, stagnation or transformation is surprisingly close to the general features of self-organizing processes in complex systems.